Moments in terms of cumulants when cumulants increase factorially - Withers, Christopher S.,; Nadarajah, Saralees, (Utilitas Mathematica, 2011)
We give new explicit expressions for central moments in terms of cumulants, tailored for random variables whose cumulants increase exponentially, like the central or non-central chi-square. We also give expressions for cumulants in terms of moments. Examples include the non-central chi-square.